Assessment of age in female population by radiographic examination of Carpal bones - Pawan A. Wankhade1, Rajesh B. Ramteke2, B.H. Tirpude3, Ninad Nagrale4, Shailesh Nagpure5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Assessment of the age of an individual from the appearance and the fusion of the ossificationcenters is a well-accepted fact in Medical and Legal professions. In the age estimation of juvenile offenders,radiological examination of bones gives valid idea of age needed in courts.Objectives: Aim was to assess the age of the ossification of carpal bones at wrist joint in females. Theobjectives were to estimate the age specific difference in all subjects, also to study difference age ofossification in central part of India with other part of country and abroad.Method: After obtaining the ethical clearance the subjects below the age of 20 years residing in centralIndia were included in this study. As per inclusion criteria carpal bones forming wrist joint were examinedradiologically with standard accepted procedures and guidelines to assess the age.Result: The outcome of this study was very fruitful and knowledgeable as it revealed age specific differenceand remarkable difference in the age of ossification as compared to the foreign countries and other parts ofIndia.Conclusion: Radiological examination plays very vital role in age estimation in judicial cases. It can beconcluded that such studies should be conducted with good sample size and at regular intervals for academicas well as in judicial point of view.